Genetic characterization of a phi80 transducing bacteriophage carrying the histidine operon of Salmonella typhimurium. - Isaki, L S (1976)
A phi 80 transducing phage, phi 80imm lambdadhis, carrying the Salmonella his-gnd region, was characterized by immunity studies, tonB deletion analysis, and marker rescue analysis. Phi 80imm lambdadhis retains the phage immunity region of the phi 80-lambda hybrid phage from which it was derived. Bacterial genes replace most late phage genes. Deletion analysis shows the prophage gene order to be immlambda-his-gnd and indicates the orientation of the his operon to be hisOGDCBHAFIE-gnd. The structure of phi 80imm lambdadhis is remarkably similar to two independently isolated phi 80 phages that carry the his-gnd region of Escherichia coli and that, like phi80imm lambdahis, were derived by directed gene transposition to the tonB locus. A derivative of phi 80imm lambdadhis that is phi 80 immune is also reported.